2015
DOI: 10.1039/c5cp03672k
|View full text |Cite
|
Sign up to set email alerts
|

SEI-component formation on sub 5 nm sized silicon nanoparticles in Li-ion batteries: the role of electrode preparation, FEC addition and binders

Abstract: Silicon is a promising negative electrode for secondary lithium-based batteries, but the electrochemical reversibility of particularly nanostructured silicon electrodes drastically depends on their interfacial characteristics, commonly known as the solid electrolyte interface (SEI). The beneficial origin of certain electrolyte additives or different binders is still discussed controversially owing to the challenging peculiarities of interfacial post-mortem investigations of electrodes. In this work, we address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
160
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(169 citation statements)
references
References 52 publications
9
160
0
Order By: Relevance
“…38 As it was reported earlier in the literature, FEC is reduced at more positive potentials than EC and EMC, thereby forming an SEI layer on the active material particles, which significantly reduces further electrolyte decomposition. [39][40][41] Cycling performance in SiG//LFP cells.-The cycling performance of the silicon-graphite electrodes (1.8-2.3 mAh cm −2 ) was investigated vs. capacitively oversized LiFePO 4 electrodes (∼3.5 mAh cm −2 ). To fully utilize the theoretical specific capacity of the different silicon-graphite electrodes, the cutoff potentials were set to 0.01 V vs. Li/Li + during lithiation (3.44 V cell voltage) and 1.25 V vs. Li/Li + during delithiation (2.2 V cell voltage).…”
Section: Resultsmentioning
confidence: 99%
“…38 As it was reported earlier in the literature, FEC is reduced at more positive potentials than EC and EMC, thereby forming an SEI layer on the active material particles, which significantly reduces further electrolyte decomposition. [39][40][41] Cycling performance in SiG//LFP cells.-The cycling performance of the silicon-graphite electrodes (1.8-2.3 mAh cm −2 ) was investigated vs. capacitively oversized LiFePO 4 electrodes (∼3.5 mAh cm −2 ). To fully utilize the theoretical specific capacity of the different silicon-graphite electrodes, the cutoff potentials were set to 0.01 V vs. Li/Li + during lithiation (3.44 V cell voltage) and 1.25 V vs. Li/Li + during delithiation (2.2 V cell voltage).…”
Section: Resultsmentioning
confidence: 99%
“…The results are discussed in context to our recent findings in alkyl carbonates as electrolyte for LIB. 32 The role of organic and inorganic compounds, in particular Li 2 O and LiF, as typical interfacial components on silicon will be highlighted.…”
Section: A558mentioning
confidence: 99%
“…From the F 1s peaks, it was observed that both Si NEs exhibited a large amount of LiF at 685 eV. 23,24 In the case of FEC addition, the peak for LiF was enhanced and a relatively large peak at ³687 eV due to C-F bonding was confirmed, indicating the presence of -CHF-OCO 2 -type compounds derived from FEC on the Si NE. In contrast, when FEC was not added, the Si NE exhibited a large number of various types of C 1s peaks derived from decomposition of the PC solvent by electrochemical reduction and an O 1s peak from a byproduct of Li 2 CO 3 at ³532 eV.…”
Section: Investigation Of Solid-electrolyte Interface Films On LImentioning
confidence: 90%
“…In contrast, when FEC was not added, the Si NE exhibited a large number of various types of C 1s peaks derived from decomposition of the PC solvent by electrochemical reduction and an O 1s peak from a byproduct of Li 2 CO 3 at ³532 eV. 23,24 From research in the field of LIBs, 25 it is well known that the PC solvent is decomposed on the Si NE surface and mainly forms a polymer-like SEI component with Li 2 CO 3 as a byproduct, which increases the charge-transfer resistance at the Si NE and deteriorates the cell Electrochemistry, 85(10), 656-659 (2017) performance, especially with respect to cyclability. Similar SEI components were confirmed for Li pre-doping without FEC; however, the chemical composition of the SEI film was changed by the FEC addition.…”
Section: Investigation Of Solid-electrolyte Interface Films On LImentioning
confidence: 99%